The chemistry of enaminones, diazocarbonyls and small rings: our contribution - Kascheres, C. M. (Soc Brasileira Quimica, 2003)
After thirty two years in Brazil and retired from Universidade Estadual de Campinas the author wishes to present this account, a summary of a large part of the research in synthetic methodology developed by the research groups of Albert J. Kascheres and the author at Universidade Estadual de Campinas Chemistry Institute. Contributions have been made to the area of enaminones, diazocarbonyls, cyclopropenones and azirines.
Keywords: enaminones; diazocarbonyls; cyclopropenones; azirines